An Unknown Copy of the Homilies by Kiev Metropolitans - Belyakova, Elena (Slavistica Vilnensis, 2019)
As a result of the study of canonical collections, it was possible to find a previously unknown manuscript of the Cycles of homilies by Kiev metropolitans of the 16th century, preserved in a copy of the beginning of the 19th century. The list was apparently made for practical purposes – to use in sermons. The language of the monument has undergone a certain russification — the scribe tried to remove the obvious traces of the “simple language” in his text.The found manuscript allows us to present the cycle of the homilies by Kiev metropolitans as a complete work. Despite its largely compilatory nature, the homilies are a valuable source on the history of the era of confessionalism in Eastern Europe. They show ways of disciplining the laypeople and clergy in conditions when Orthodoxy did not have direct government support. The period of the 16th century is sparingly consecrated by the sources of the Kiev Metropolis – which makes the study of the homilies of the Kiev metropolitans of this period more valuable.
Keywords: Kiev metropolis; lectures of metropolitans; collection of manuscripts of Barsov; confessionalization; Zhirovitsky monastery